Features of the Taxation in the Territories with the Special Mode of Business and Investing Activities: Comparative Analysis of the Russian and Foreign Best Practices - Anatolievich Smirnov, Dmitry; Aleksandrovich Strus, Konstantin; Artemovna Avanesova, Anna (International Journal of Engineering and Technology, 2018)
Preferential taxation regimes are recognized in the modern developed states as the most effective way of stimulation of entrepreneurial and investment activity. We examined the Russian mechanism of establishment of the preferential taxation regimes that have been developed for entrepreneurial and other investment activities and their infrastructure designed to provide mechanisms of operations. Our comparative analyses of the best practices in preferential taxation regimes across developing countries inform readers about advantages and risks of the investment activities and organization of business in certain territories of modern Russia. Critical appraisal of theories and practices in the formation of specific preferential taxation regimes would assist readers in the implementation of entrepreneurial and investment activity in modern Russia, revealing features of optimal regimes for specific businesses with possible mitigation or prevention of financial risks for investors. Critical comparative analysis of the best foreign practices in China, Singapore, and United Arab Emirates in the organization of foreign businesses sheds light on the most effective forms of such investment activities.Incompleteness and fragmentariness of the Russian legislation supporting preferential taxation regimes prevent successful implementation of foreign entrepreneurial and investment activities.The Russian legislation must be revised to ensure an attractive environment for foreign investments. Successful business and innovative activities would be possible only by the realization of the following legally significant steps: 1) adoption of the basic legislation 2) statewide programs supporting the development of free economic zones of advanced economic development.Â Â